2016
DOI: 10.1080/14656566.2016.1182155
|View full text |Cite
|
Sign up to set email alerts
|

Integral pharmacological management of bone mineral disorders in chronic kidney disease (part I): from treatment of phosphate imbalance to control of PTH and prevention of progression of cardiovascular calcification

Abstract: Improvements in CKD-MBD require an integral approach, addressing all three components of the CKD-MBD triad. Individualization of treatment with P-binders and combinations of anti-parathyroid agents may improve biochemical control with lower incidence of undesirable effects. Isolated biochemical parameters do not accurately reflect calcium or P load or bone activity and do not stratify high cardiovascular risk patients with CKD. Initial guidance is provided on reasonable therapeutic strategies which consider th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 142 publications
(215 reference statements)
0
6
0
Order By: Relevance
“…Similar effects were described for ghrelin, a neuropeptide hormone that regulates appetite with opposite effects to leptin 12 . In contrast, parathyroid hormones exacerbate calcification by increasing the circulating levels of available calcium and phosphate 1315 . Although some hormone therapies have proven to be effective in ameliorating vascular calcification in animal models, their clinical application is limited by serious adverse side effects that accompany the requirement for chronic administration.…”
Section: Introductionmentioning
confidence: 99%
“…Similar effects were described for ghrelin, a neuropeptide hormone that regulates appetite with opposite effects to leptin 12 . In contrast, parathyroid hormones exacerbate calcification by increasing the circulating levels of available calcium and phosphate 1315 . Although some hormone therapies have proven to be effective in ameliorating vascular calcification in animal models, their clinical application is limited by serious adverse side effects that accompany the requirement for chronic administration.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the high prevalence of cardiovascular calcifications in CKD, even in ND-CKD patients ( 20 , 21 , 26 30 ), with a greater severity ( 20 , 31 ) and more rapid progression ( 32 , 33 ). Furthermore, it has been suggested that these cardiovascular calcifications may be not only a useful prognostic tool but also relevant in guiding therapeutic interventions ( 19 , 34 , 35 ), as it will be reviewed in section Treatment Implications. However, we will first let readers understand the different diagnostic methods and the important contribution of CKD-MBD-related aspects in the pathophysiology of VC in CKD patients (section Pathophysiology of CKD-MBD-related Vascular Calcification).…”
Section: Chronic Kidney Disease-mineral and Bone Disorders (Ckd-mbd) And Vascular Calcificationmentioning
confidence: 99%
“…Although VC is a surrogate marker and is not yet considered a treatment target in CKD ( 108 ), the presence of VC may have important therapeutic implications ( 34 , 35 , 44 ), unless all patients are treated with the mindset of reducing the incidence or progression of VC (i.e., using all minimization strategies such as reducing exogenous Ca and P).…”
Section: Treatment Implicationsmentioning
confidence: 99%
“…Humans are ‘informavores’ [ 36 ], and in an era in which we have moved from ignorance to info xication [ 37 , 38 ], an increasingly sophisticated hierarchy of evidence and systematic summaries of the best evidence to guide care are of the utmost importance ( Figure 3 ). However, in the case of CKD–MBD (and most areas of nephrology), the level of evidence is poor or extremely poor; nevertheless, we are required to act [ 42–44 ].…”
Section: Kdigo Ckd–mbd Guidelinesmentioning
confidence: 99%